Identifying delay factors in electrical distribution projects at Eskom Northern Cape Operating Unit - Ntshangase, Bonga (Department of Construction Economics and Management, 2018)
Delays on electrical engineering projects are a phenomenon at Eskom distribution due to a wide range of causes. These project delays result in Eskom to contravene with Electricity Regulation Act 4 of 2006 in terms of providing efficient, effective and sustainable operation of electricity supply infrastructure, promoting the use of renewable energy sources and energy efficiency as well as to facilitate universal access to electricity for South African consumers (Gazette, 2006). Eskom strives to comply with the Electricity Regulation Act by initiating and implementing strengthening projects, refurbishment (reliability) projects, direct customer projects, infills projects and electrification projects (Eskom, 2014).The severe delays experienced in the delivery of electrical distribution projects have a negative impact on South African economic growth and population. This research study adopted interactive management methodology for the identification of project delay factors in Eskom distribution projects through the use of the idea writing technique, nominal group technique, and interpretive structural modelling technique. The interactive management methodology allows a group of people collaboratively to develop a structure that defines the relationship among the system elements. Using interactive management approach, a total of one hundred and twelve project delay factors were reduced to twenty six significant project delays which formed part of interpretive structural modelling. This research study revealed the hierarchical model illustrating interrelationships between the twenty six identified project delay factors. The research study identified three root causes of delays in electrical distribution projects at Eskom Northern Cape Operating Unit, namely "poor communication", "poor planning", and "project scheduling not properly done". The three identified root causes can be used as critical points for eradicating delays in electrical distribution projects at Eskom Northern Cape Operating Unit. The research study found that a total of ten out of twenty six project delay factors were unique to electrical distribution projects at Eskom Northern Cape Operating Unit.